Influence of the angle of cut of workpiece on taper and corner roundness during Wire Electrical Discharge Machining (WEDM) - Khan, Ahsan Ali; Al Hazza, Muataz Hazza Faizi; Mohiuddin, A. K. M.; Ali, Mohammad Yeakub (Praise Worthy Prize Publishing House, 2017)
Wire electrical discharge machining (WEDM) is a unique machining technique which is capable of machining parts with high degree of complexity regardless of their hardness. However, when high precision and accuracy are needed, the taper and corner roundness on the workpiece machined need to be controlled to ensure that the parts can perform their intended function. Parameters such as angle of the profile cut; peak current (IP) and wire speed (WS) might affect the taper and the corner roundness of the machined workpiece. To know the sharpness of the profile, the corner roundness and taper of the kerf should be assessed. Hence, to assess the influence of IP and WS on angle of the profile cut, the design of experiment (DOE) was used for this investigation. By employing full factorial design of DOE, eight runs were conducted for each of the responses which are corner radius and taper angle. The experiments were performed by using brass as the wire electrode and stainless steel 304 (SS 304) as the workpiece. The taper (in terms of angle) is calculated by using the value of kerf width at the top and bottom of the cut. The corner roundness was also measured using a measuring microscope. It was found that the degree of angle of cut and IP have a significant effect on taper angle and corner roundness while the significance of WS is low. From the analysis, it is found that the optimum value of the angle of the cut, IP and WS are 117.47°, 5.00A and 10.00 mm/s respectively. By knowing the significance of the angle of the profile cut, IP, and WS and the optimum values, the profile with low taper and sharp corner can be achieved.